Demokrasi Deliberatif: Pelaksanaan Musrenbang di Desa Pengujan Kabupaten Bintan Tahun 2022 - Vivin Titin Rahmayanti; Riza Safriya Hastika; Ardi Putra; Rizky Octa Putri Charin (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
This paper discusses democratic considerations in implementing development planning considerations in Pengujan Village without the overall participation of the community, therefore the aim of this study is to identify factors leading to low community participation in performing musrenbang in Pengujan Village. Descriptive qualitative research method with observational and interview data collection techniques. From the results of the study, it can be seen that the implementation of Pengujan Musrenbang Village is in accordance with Law No. 6 of 2014 regarding the village government which stipulates that the implementation of Musrenbang must match the potential of the village, Pengujan Village has potential capacity in the marine sector with the majority of the population being fishermen, but the level of community participation in general is not high due to a number of factors including saturation of communities as their previous aspirations have not been fulfilled, activities of fishermen whose working hours cannot be ascertained due to changing sea conditions, and information on discussions at village and village levels has not been distributed equally to all people. Keywords: democrasi deliberation, musrenbang, partisipation, village potencial